A bead on a rotating rod experiment. (18th June 2021) - Cross, Rod
Abstract: Experimental results are presented concerning a bead sliding on a rotating, horizontal rod. If the rod rotates at constant angular velocity then the sliding speed in the radial direction increases exponentially with time, provided that the rotation speed is sufficient to overcome friction. Otherwise the bead rotates in a circular path of constant radius.